Prognostic Value of Interval Between the Initiation of Neoadjuvant Treatment to Surgery for Patients With Locally Advanced Rectal Cancer Following Neoadjuvant Chemotherapy, Radiotherapy and Definitive Surgery - Wan, Xiang-Bo; Zhang, Qun; Chen, Mo; Liu, Yanping; Zheng, Jian; Lan, Ping; He, Fang (Frontiers in Oncology, 2020)
Background: Both the addition of more intensive preoperative chemotherapy and the use of a longer waiting period between radiotherapy and total mesorectal excision (TME) surgery lengthen the time interval from the initation of treatment to definitive surgery in patients with locally advanced rectal cancer (LARC). We aimed to determine the impact of these longer intervals on oncological outcomes. Methods: A total of 2267 patients who received intensive chemotherapy, radiotherapy, and TME surgery for LARC between January 2010 and December 2018 were studied retrospectively. Patients were divided into 4 groups based on total-time-to surgery (interval between initiation of treatment and TME surgery, TTS): <13 weeks (TTS-1), 13 to <15 weeks (TTS-2), 15 to <17 weeks (TTS-3), ≥17 weeks (TTS-4). Overall survival (OS), disease-free survival (DFS), distant metastasis-free survival (DMFS), and local recurrence-free survival (LRFS) rates in different TTS groups were compared, and survival hazard ratios (HR) for different demographic and clinicopathological variables, including TTS, were calculated to determine their prognostic significance. Results: Mean follow-up was 42.0 (range, 5-162) months. The 3-year OS, DFS, DMFS, and LRFS rates were 87.0%, 79.4%, 80.9% and 93.8%, respectively. OS, DFS, and DFMS rates differed significantly between different TTS groups (P=.010, P<.001, and P<.001, respectively), and these differences were primarily related to lower survival rates in patients in the shortest TTS group (TTS-1). The only significant positive independent prognostic factor for 3-year DFS was a longer TTS (TTS 2-4 vs. TTS-1; HR 0.884, 95% CI 0.778-0.921, P<.001), and the significant negative independent prognostic factors were moderate to poor tumor differentiation (vs. well-differentiated; HR 1.191, 95% CI 1.004-1.414, P=.045) and clinical N1-2 stage (vs. N0 stage; HR 1.190, 95% CI 1.052-1.347, P=.006). Conclusion: In patients with LARC who are receiving intensive chemotherapy, radiotherapy, and TME surgery, an interval between the initiation of treatment and the performance of surgery of longer than 13 weeks is associated with preferable disease-free survival outcomes.